2012
DOI: 10.1136/injuryprev-2011-040261
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Vietnamese A6 mortality reporting system: injury as a cause of death

Abstract: The A6 mortality reporting system is embedded within the commune health system and is the lead mortality reporting system for the Ministry of Health. The system performs well in relation to its completeness and classification of injury related deaths. With further enhancements and ongoing support from government and donor agencies, the A6 system will be a valuable resource for identifying and planning preventive strategies targeting the leading causes of injury related deaths in Vietnam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 5 publications
(4 reference statements)
0
20
0
Order By: Relevance
“…16 Until now, the most recent study was the National Health Suvey 28 (n = 2481), which was undertaken 12 years ago and a VA study (of only 189 deaths) in FilaBavi. 9,23 It is important to consider the limitations of this study when interpreting the findings-namely, the study relied on the recall of events by household members (34% of the 5613 cases had not been admitted to hospital) 10 and by accessing hospital records to develop the VA databases; each has well-documented limitations in relation to capturing the leading causes of death. 9,18 As highlighted, the study was undertaken in only 3 provinces (there are a total of 63 provinces in Viet Nam), yet despite the few provinces captured, we selected provinces that represented the geographic distribution of Viet Nam, with Bac Ninh in the northern red delta river region, Lam Dong in the central highlands region, and Ben Tre in the southern Mekong delta region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Until now, the most recent study was the National Health Suvey 28 (n = 2481), which was undertaken 12 years ago and a VA study (of only 189 deaths) in FilaBavi. 9,23 It is important to consider the limitations of this study when interpreting the findings-namely, the study relied on the recall of events by household members (34% of the 5613 cases had not been admitted to hospital) 10 and by accessing hospital records to develop the VA databases; each has well-documented limitations in relation to capturing the leading causes of death. 9,18 As highlighted, the study was undertaken in only 3 provinces (there are a total of 63 provinces in Viet Nam), yet despite the few provinces captured, we selected provinces that represented the geographic distribution of Viet Nam, with Bac Ninh in the northern red delta river region, Lam Dong in the central highlands region, and Ben Tre in the southern Mekong delta region.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, no systematic evaluation of the A6 system has been undertaken in relation to all-cause mortality or to enumerate (subject to its robustness) age-standardized mortality rates (ASRs) for all causes of death. The proposed study, therefore, assesses the completeness, sensitivity, and positive predictive value of the system in relation to all-cause mortality and estimates the age-specific mortality rates for Viet Nam.…”
mentioning
confidence: 99%
“…Previous studies have validated the data from the A6 system, demonstrating that they are of good quality. 13,14 In this study, we obtained data from the HCM City health department for January 1, 2010, through December 31, 2013, which included data from 322 community health centers in 24 districts of HCM City. The data contain 101 897 mortalities, with information about the date of death, sex, age, and cause of death as classified by the International Classification of Diseases, 10th Revision (http://apps.who.int/ classifications/icd10/browse/2016/en).…”
Section: Data Source and Qualitymentioning
confidence: 99%
“…The majority of VA reports are not completed by doctors or medically trained people resulting in concerns about the accuracy of VA data 2–4. The General Statistics Office of Vietnam currently publishes VA reports via the A6 Mortality Reporting System to identify the number of deaths and their causes 5. Limited data are also available from three mortality databases for children 6.…”
Section: Introductionmentioning
confidence: 99%
“…A 2012 study of 5273 deaths in Vietnam recorded by the A6 Mortality Reporting System (reliant on VA reports) found 14% of deaths were caused by injuries (n=763/5273), with an overall injury mortality rate of 55.3 persons per 100 000 person-years 11. A study of 2800 households in seven districts in Hanoi found deaths from an injury were the leading cause of death for children aged under 18 years 12.…”
Section: Introductionmentioning
confidence: 99%